2008
DOI: 10.1097/01.nnr.0000313490.56788.cd
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Parenting Self-efficacy

Abstract: Birth perception is a correlate of parenting self-efficacy that is modifiable; therefore, nurses have an opportunity to strive to create a positive birth experience for all women to enhance their early parenting self-efficacy. Nurses can also consider assessing women at risk for suboptimal parenting self-efficacy and intervene through teaching, support, and parenting self-efficacy boosting interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 38 publications
(51 reference statements)
6
35
2
Order By: Relevance
“…In studies with breast cancer patients and postpartum women, age was significantly associated with self-efficacy. 2629 This study also showed concordance result that age was a significant predictor of self-efficacy. It is considered that people at older age have experienced diverse situations that expanded the scope of their understanding, and it caused positive effect on self-efficacy.…”
Section: Discussionsupporting
confidence: 79%
“…In studies with breast cancer patients and postpartum women, age was significantly associated with self-efficacy. 2629 This study also showed concordance result that age was a significant predictor of self-efficacy. It is considered that people at older age have experienced diverse situations that expanded the scope of their understanding, and it caused positive effect on self-efficacy.…”
Section: Discussionsupporting
confidence: 79%
“…An important finding from Keen et al's study was that parents who received additional support (in the form of a two-day parent group workshop and a series of ten home based consultations), compared to those who received information only, were more likely to achieve a reduction in parenting stress and an increase in their sense of PSE. These findings are consistent with both selfefficacy theory and previous PSE research, which has found positive predictive relations between parental perceptions of support in their parenting role and their perceptions of PSE (Bandura, 1997;Bryanton, Gagnon, Hatem, & Johnston, 2008;Cutrona & Troutman, 1986;Weiss, 2002). However, not all support is equally effective, and the support that parents receive from formal professional services has been found to have less influence on their sense of PSE than support they receive from informal sources, such as family and friends (Benson, 2006;Dunn, Burbine, Bowers, & Tantleff-Dunn, 2001;Ekas, Lickenbrock, & Whitman, 2010;Rodrigue, Morgan, & Geffken, 1992;Saloviita, Italinna, & Leinonen, 2003).…”
Section: Introductionsupporting
confidence: 92%
“…Prior work conducted with mothers has demonstrated that multiparas report higher levels of parenting self-efficacy when compared with primiparas (Bryanton, Gagnon, Hatem, & Johnston, 2008). Less is known, however, about fathers.…”
Section: Discussionmentioning
confidence: 99%